2020
DOI: 10.1186/s40164-020-00190-2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering better chimeric antigen receptor T cells

Abstract: CD19-targeted CAR T cells therapy has shown remarkable efficacy in treatment of B cell malignancies. However, relapse of primary disease remains a major obstacle after CAR T cells therapy, and the majority of relapses present a tumor phenotype with retention of target antigen (antigen-positive relapse), which highly correlate with poor CAR T cells persistence. Therefore, study on factors and mechanisms that limit the in vivo persistence of CAR T cells is crucial for developing strategies to overcome these limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 135 publications
0
81
0
Order By: Relevance
“…How to convert exhausted T cells into active T cells is a problem that many scientists are trying to solve. In hematological malignancies, CAR-T cell therapy has impressive therapeutic efficacy [ 52 ]; however, it also faces the drawback that CAR-T cells lose their effects due to rapid exhaustion after injection into patients [ 37 , 52 ]. On this issue, TOX might be used as a specific target to reverse T cell exhaustion by reducing its expression activity, which can maintain the effects of CAR-T cells in patients for a longer period of time.…”
Section: Conclusion and Further Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…How to convert exhausted T cells into active T cells is a problem that many scientists are trying to solve. In hematological malignancies, CAR-T cell therapy has impressive therapeutic efficacy [ 52 ]; however, it also faces the drawback that CAR-T cells lose their effects due to rapid exhaustion after injection into patients [ 37 , 52 ]. On this issue, TOX might be used as a specific target to reverse T cell exhaustion by reducing its expression activity, which can maintain the effects of CAR-T cells in patients for a longer period of time.…”
Section: Conclusion and Further Directionsmentioning
confidence: 99%
“…T cell exhaustion is a term used to describe T cells under chronic antigen stimulation that alter or lose their effector function, and this is related to abnormal expression of immune checkpoint proteins in T cells [ 35 37 ]. Recently, many studies have shown that TOX is a crucial transcription factor involved in exhaustion of CD8+ T cells [ 1 , 2 , 4 , 32 , 38 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…CAR-T therapy can be broadly grouped into three groups: single-target, multi-target, and universal CAR-T (Table 2 ). The ideal therapeutic CAR-T targets a cell surface antigen that is preferentially, and ideally exclusively, expressed on myeloma cells [ 37 ]. Resistance mechanisms such as “on target off tumor” recognition (expression of targeted antigens on normal cells) and “antigen escape” (loss of targeted antigens on tumor cells) pose ongoing therapeutic challenges in CAR-T therapy [ 38 ].…”
Section: Chimeric Antigen Receptor (Car)-t Cellmentioning
confidence: 99%
“…Cancer immunotherapy has been a game changer in cancer treatment since the approval of the immune checkpoint inhibitor (ICI), ipilimumab, in 2011 and subsequent anti-PD-1 antibody, pembrolizumab and nivolumab in 2014 [ 1 – 5 ]. Currently, 10 immune checkpoint inhibitors and 5 chimeric antigen receptor T cell (CAR-T) products have been approved in treating 17 types of malignant diseases and two tissue-agnostic indications across the world [ 6 12 ]. CD19-targeted CAR-T cell therapy for B cell neoplasms has opened up a new era in synthetic cancer immunotherapy [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%